Penerapan Model Numbered Heads Together menggunakan Media Board Game dalam Meningkatkan Pemahaman Materi Pengukuran Waktu di Kelas 3 SD - Risyda Dzul Fadlilah; Muhammad Junaidi Retno Manggolo; Syailin Nichla Choirin Attalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve the understanding of third grade elementary school students on time measurement material through the application of the Numbered Heads Together (NHT) learning model with board game media. The main problem in conventional learning is the low active involvement of students and the difficulty in understanding the concept of time concretely. This research is a Classroom Action Research (PTK) conducted in two cycles using the Kemmis and McTaggart model. The research subjects were 23 third grade students of SDN 1 Langon, Jepara. Data collection techniques included observation, interviews, tests, and documentation. The results showed a significant increase in student understanding, which was marked by an increase in the average score from 65.3 in the pre-cycle to 85.3 in cycle I, as well as an increase in learning completeness from 40% to 68%. Students were more active in discussions, motivated, and able to explain the concept of time independently. The NHT and board game model creates a collaborative and fun learning atmosphere and supports students' cognitive, social and emotional development. These results prove that educational game-based learning strategies are effective in improving the understanding of abstract mathematical concepts, especially time measurement.